Constructing and standardizing Interception and Passing Among four Attackers in Handball Primer League Players - Hamel, Saad Dari; Ahmed, Zahra Shehab (Journal of Physical Education, 2021)
The researchers aimed at designing and constructing, and standardizing a test for interception and passing among four attackers for primer league handball players. The researchers used the descriptive method on (103) primer handball league players of the season 2020 – 2021 from 11 clubs participating in the primer league. A pilot study was conducted on (5) players from (Al Talaba club) then (18) players from Al Koot club were selected for experimental bases, other formed standardizing subjects. The researchers concluded that the test is objective and they recommend using this test for evaluating players as well as for payers’ selection within clubs and international teams of handball. They finally recommended using these tests on other age groups and skills.